Selection of the Optimum Seed and Media Sterilization Techniques for Muna Teak (Tectona grandis L.) Micropropagation - Ratna Uli Damayanti Sianturi; Yulianti Bramasto; Naning Yuniarti; Muhammad Zanzibar; NFN Megawati (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2020)
The existence of the muna teak (Tectona grandis L.), is currently threatened with extinction, so a muna teak replanting program is needed. Micropropagation techniques can be one solution for the supply of high quality seedlings. The purpose of this study was to obtain the optimum sterilization technique to get the sterilize explants of muna teak and to get the suitable media for in vitro multiplication. The study was conducted in a tissue culture laboratory of the Forest Tree Seed Technology Research and Development Centre in Bogor. This study consisted of two stages and the experimental design used was a completely randomized design. The first phase of the study was the treatment of sterilization techniques consisted of soaking explants in various concentration of clorox solution and the second stage of the study was the treatment of multiplication media. The results showed that the proper sterilization technique to obtain sterilize explants of muna teak seedlings was immersed in 20% chlorox solution for 10 minutes, then immersed in 15% of chlorox for 15 minutes. The best medium for the induction stage and multiplication of Muna teak buds which are modified media plus Benzyl Amino Purine (BAP) hormone as much as 0.1 mg.l-1